Komunikasi Birokrasi LABKESDA Kabupaten Solok dalam Pengawasan Depot Air Minum Isi Ulang - Elnita Elnita; Ernita Arif; Asrinaldi Asrinaldi (IAI Darussalam, 2020)
This study aims to see the implementation of bureaucratic communication at the Labkesda Solok Regency in monitoring the quality of refill drinking water. This type of research is a qualitative approach with descriptive methods using informants as well as observation techniques, interviews, and documentation studies. The analytical tools used are induction analysis, deduction analysis, classification, and verification. Labkesda guides persuasive bureaucratic communication to drinking water depot owners. The communication that is built fulfills a regulatory function, namely ensuring the implementation of applicable regulations. Continuous communication between the government and drinking water depot owners is the main key in maintaining and increasing the compliance of drinking water depot owners. Labkesda carries out comprehensive bureaucratic communication by running formal communication channels with relevant stakeholders so that there is an increase in the compliance of drinking water depot owners in checking the quality of the drinking water they sell